Clinical impact of CT coronary angiography without exclusion of small coronary artery segments: a real-world and long-term study. Issue 1 (7th May 2020) - Logghe, Yannick; Van Hoe, Lieven; Vanhoenacker, Piet; Bladt, Olivier; Simons, Philip; Kersschot, Erik; Van Mieghem, Carlos
Abstract : Objectives: CT coronary angiography (CTCA) has become a valuable diagnostic test in the workup of patients with possible coronary artery disease (CAD). Because of inherent limitations in spatial resolution, epicardial vessels with a small diameter, in general less than 1.5–2 mm, have so far been excluded in studies assessing clinical utility of CTCA. This study sought to assess the clinical impact of CTCA taking into account pathology in small coronary arteries. Methods: We conducted a retrospective cohort study of all patients with possible CAD who underwent dual-source CTCA and subsequent invasive coronary angiography (ICA) between January 2010 and July 2017. Patients with an Agatston calcium score ≥1000 were reported separately. Diagnostic accuracy of CTCA on a patient, vessel and segment level was calculated. The physician's therapeutic decision was defined as conservative, medical antianginal treatment or revascularisation. Using ICA as the reference, we calculated the precision of CTCA to replicate these therapeutic recommendations. Results: In total, 1209 patients underwent both CTCA and ICA. Overall diagnostic performance of CTCA showed a sensitivity of 90% (95% CI 86% to 93%) and specificity of 40% (95% CI 36% to 45%). With regard to clinical decision making, CTCA showed good performance: 91% of patients who were treated medically or by revascularisation were correctly identified. Prevalence of disease in small vessel segments was low: 16% showed significant CAD on ICA. Prevalence of significant disease was 70% in patients with an Agatston score ≥1000: the majority underwent revascularisation. Conclusions: From a true patient perspective, without exclusion of smaller coronary artery segments, CTCA allows safe patient management.